Assessment of Factors Exerting Effects on Strength of C5/8 - C90/105 Concrete in the Case of Fire - G. I. Kasperov; I. I. Polevoda; M. N. Ryskin (Наука и техника)
Taking into account the approach which is given in the Belarussian Construction Norms adopted on 05.03.2001 the paper shows the main principles which are recommended for determination and assessment of the concrete strength in the case of fire. On the basis of investigations pertaining to the influence of various factors on the strength of C5/8 - C90/105 concrete in the case of short high-temperature heating a mathematical model has been proposed to determine coefficient of concrete behaviour in the case of fire.